(untitled) - Henslowe, Philip (Cambridge, 2002)
The Diary of Philip Henslowe, owner of the Rose Theatre in London, remains the most valuable source of information about the workings of the Elizabethan public theatres. The diary deals with the daily activities of the companies of players who performed at the Rose. The 1961 edition has long been out of print. For this second edition RA Foakes has added a new preface and bibliography to the original: a thorough introduction to the manuscript, a transcription of the document itself, several indexes and photographs of the original manuscript.
Keywords: Nhà hát,Theatrical managers,Theater,Quản lý sân khấu; Lịch sử,History; Thế kỉ 16,16th century; Anh quốc,Great Britain,England,Anh quốc